Priljubljenost športnorekreativnih dejavnosti v povezavi s spolom in izobrazbo - Dolenc, Maja (Šport (Ljubljana), 2010)
The aim of the study was to investigate the most popular sport activities among Slovenian population according to gender and education. The sample in the year 2008 (17th study of SJM) consisted of 1286 persons aged 15 years and above (average age 46,6 18,9 years), 54 % were women and 46 % were men. They filled in a questionnaire about their sport activities. The results show that both men and women prefer to walk, swim and cycle. The same results were gained when we took different level of education into account. Women also like mountaineering (15 %), aerobics (13 %) and alpine skiing (13 %) while men prefer to play football (22 %), go to ski (21 %) and play basketball (15 %).
Keywords: izobrazba; odrasli; raziskave; rekreacija; Slovenija; spol; šport; športna aktivnost